Role of inter-institutional partnerships in promoting holistic employee wellness programs: A convergent mixed-methods study across three public universities in Metro Manila, Philippines - Rosalie Dela Cruz (CV Rezki Media, 2025)
Background: Employee wellness has become an increasingly essential concern in higher education; yet, many public universities continue to struggle with implementing comprehensive and sustainable wellness initiatives. Inter-institutional partnerships offer opportunities to strengthen these efforts through shared resources and coordinated programming. Objectives: This study examined how such partnerships support the development of holistic employee wellness programs across three public universities in Metro Manila. Methods: Using a convergent mixed-methods design, quantitative data were collected from 150 employees through an 18-item validated survey and analyzed using descriptive statistics and chi-square tests to assess institutional differences in awareness, participation, and perceived effectiveness. Qualitative data from six key informants were analyzed using grounded theory techniques to identify themes related to institutional practices and collaborative mechanisms. Results: Findings indicated significant variations among institutions in employee awareness, participation levels, and perceptions of program effectiveness. Despite the availability of wellness initiatives, participation remained limited, mainly due to workload demands, time constraints, and scheduling challenges. Qualitative themes highlighted four central factors influencing the implementation of wellness: institutional support, holistic wellness orientation, program personalization, and persistent participation barriers. These themes helped explain why engagement levels differed among institutions. Conclusions: Overall, inter-institutional collaboration contributes positively to wellness program development, but its impact depends on strong institutional support, program relevance, and clear communication. Enhancing coordination and tailoring activities to employee needs may improve future wellness outcomes.